Analisa Manajemen Strategik Pt Fondaco Jayatama Dalam Bersaing - Mauren Astria; Eko Harry Susanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
To support the improvement of dental health in the community it is necessary to overcome them. The efforts of PT Fondaco on the fact encourage the founder to become one of the suppliers who support a variety of dental experts in the treatment by providing various medical purposes.The purpose of this research is to analyze the influence of external environment, and internal to competitiveness and analyze the competitive strategy of PT Fondaco Jayatama to improve competitiveness. The method used in this research is qualitative descriptive method by doing SWOT analysis (EFE and IFE matrix), IE matrix in matching stage, and QSPM analysis in desicion stage. The results of the EFE and IFE matrix analysis showed that Fondaco Jayatama can used all the opportunities and can overcomed threats from the rivalry. PT Fondaco Jayatama also has a good internal and can not be down by the external environment. PT Fondaco Jayatama was a strong competitors. The conclusion of this research is product development strategy is the best strategy to be apply in the organization.